Ilex pedunculosa Longstalk Holly - Edward Gilman (EDIS)
This document provides an overview of the longstalk holly (Ilex pedunculosa), a broadleaf evergreen native to China, Japan, and Korea. It describes the plant’s characteristics, including its moderately dense habit, smooth undulating leaves, and small bright fruits. The longstalk holly is noted for its ornamental features, such as its pyramidal silhouette, pleasant fragrance, and persistent red fruits that attract birds. The document also covers the plant’s growth requirements, including its preference for well-drained soil and partial shade, as well as its tolerance to wind and cold. Additionally, it highlights the plant’s potential uses in landscaping, such as hedges, screens, and container plantings. Original publication date October 1999.